Calculate the silicon energy gap using Fermi Dirac integration (Latakia University Journal -Basic Sciences Series, 2020)
using quantum statistics and Fermi-Dirac distribution was calculated the silicon energy gap width by temperature and density of charge carriers in the conductivity band. The density in the equilibrium state and the effect of the energy gap width were calculated. We drew the curves by taking the energy field value of the silicon specific threshold and derived the known experimental values. and the theoretical results obtained were compared with the available experimental results in this field.